Use of di-(2-ethylhexyl)-orthophosphoric acid for the extraction of lanthanum, neodymium, samarium and yttrium from nitric acid solutions - Alexandrovich, Karelin Vladimir; Kieu, Bach Thuan; Le , Hai Son; Vladimirovna, Karelina Nadezhda (Nuclear Science and Technology, 2026)
The process of separating rare-earth elements into individual components is considered the most important problem in rare-earth technology because of the similarity in their physical and chemical properties. Currently in the world dialkyl phosphate compounds are widely used as effective extractors for rare earths. However, most extraction processes have been studied from hydrochloric acid or perchlorate solutions. In Russia, tributyl phosphate has long been used to extract rare earths from nitric acid solutions, but the distribution coefficients of the elements are not high, and the process must be repeated multiple times. In this study di-(2-ethylhexyl)-orthophosphoric acid was used for the extraction of lanthanum, neodymium, samarium, and yttrium from nitric acid solutions. When the concentration of nitric acid increased, distribution coefficient of elements gradually decreased to minimum (in the range of 1 to 5M) then increased backward. However, when the concentration was too high (C > 5M), nitric acid was extracted to the organic phase due to the properties of the phosphoryl group. Moreover, the study of dependence of solvation number of neodymium on the concentrations of nitric acid shows that rare earths in the organic phase can be extracted as Re(HA2)3 (C < 1M) or Re(NO3)3«3HA (C > 5M).